Sistem Informasi Pengolahan Data Pedagang dan Retribusi pada Pasar Seketeng Kabupaten Sumbawa - Azzahratun Jannah, Linda; Esabella, Shinta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Seketeng Market is one of the traditional markets as a center for economic and social activities for the community in Sumbawa Regency, West Nusa Tenggara, which is under the auspices of the Diskoperindag. The use of digital technology in managing data and fees at Seketeng Market is still done manually. This research aims to design and develop an information system for managing trader data and levies at Seketeng Market, Sumbawa, which aims to produce a web-based application with an attractive appearance with features, namely trader data management menu, levy management menu, report and monitoring menu. The data collection methods used were observation, interviews and literature study methods. This application was built using the prototype software development methodology, with black box testing. The results of this research are a web-based information system for managing trader data and fees at the Seketeng Market in Sumbawa. It is hoped that this application will be able to increase efficiency and accuracy in managing trader data and levies at Seketeng Market and facilitate reporting and monitoring of payments by market managers.